2014
DOI: 10.1038/srep05240
|View full text |Cite
|
Sign up to set email alerts
|

A novel proteasome inhibitor suppresses tumor growth via targeting both 19S proteasome deubiquitinases and 20S proteolytic peptidases

Abstract: The successful development of bortezomib-based therapy for treatment of multiple myeloma has established proteasome inhibition as an effective therapeutic strategy, and both 20S proteasome peptidases and 19S deubiquitinases (DUBs) are becoming attractive targets of cancer therapy. It has been reported that metal complexes, such as copper complexes, inhibit tumor proteasome. However, the involved mechanism of action has not been fully characterized. Here we report that (i) copper pyrithione (CuPT), an alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 43 publications
2
79
0
Order By: Relevance
“…Inhibition of USP14 increased the turnover of oxidized and damaged proteins by the proteasome (60). In addition, the therapeutic importance of inhibiting USP14 and UCHL5 have been demonstrated for controlling progression of acute myeloid leukemia (63,64) or tumor growth (93). Although its roles in cell viability, life span, and cancers (94 -96) make it a promising drug target (62), there are currently no specific inhibitors for the Rpn11 metalloprotease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of USP14 increased the turnover of oxidized and damaged proteins by the proteasome (60). In addition, the therapeutic importance of inhibiting USP14 and UCHL5 have been demonstrated for controlling progression of acute myeloid leukemia (63,64) or tumor growth (93). Although its roles in cell viability, life span, and cancers (94 -96) make it a promising drug target (62), there are currently no specific inhibitors for the Rpn11 metalloprotease.…”
Section: Discussionmentioning
confidence: 99%
“…Although its roles in cell viability, life span, and cancers (94 -96) make it a promising drug target (62), there are currently no specific inhibitors for the Rpn11 metalloprotease. An ability to study individual proteasome-associated DUBs in isolation should facilitate intensive ongoing drug discovery efforts (61,63,93,(97)(98)(99) relative to the dynamic, ATP-dependent, multisubunit proteasome complex.…”
Section: Discussionmentioning
confidence: 99%
“…Copper ions or copper-containing agents have been largely investigated for their ability to inhibit UPS function in cancer cells [8][9][10]. Copper complex CuPT can induces cancer cell death through targeting both 19S proteasomal DUBs and 20S proteasome peptidases [10], which is distinct from the clinical used proteasome inhibitor bortezomib.…”
Section: Discussionmentioning
confidence: 99%
“…Several copper-binding agents have been investigated for their ability to bind copper and impair UPS function in malignant cells [8][9][10]. We have previously demonstrated that copper pyrithione (CuPT), a copper complex used as antifouling paint biocides, induces cancer cell death by targeting both 19S proteasomal DUBs and 20S proteasome peptidases [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation